DIGITAL EDUCATIONAL MODEL: TRANSFORMATION TOWARDS A DISTANCE UNIVERSITY EXPERIENCE (Proceedings of the International Conference on Education, 2021)
Dataset does not exist anymore: Lopez, M., Peddinani, B. K., & Carrion, B. (2021, October). Digital Educational Model: Transformation towards a Distance University Experience. In Proceedings of the International Conference on Education (Vol. 7, No. 1, pp. 559-565).The dataset with the identifier http://doi.org/10.17501/24246700.2021.7155 was withdrawn
Keywords: higher education; educational innovation; professional education; distance education; pandemic adaptation